2018
DOI: 10.1038/s41598-018-30609-0
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor Prediction Errors Modulate EEG Activity Over Parietal Cortex

Abstract: The parietal cortex is thought to be involved in visuomotor adaptation, yet it remains unclear whether it is specifically modulated by visuomotor prediction errors (i.e. PEs; mismatch between the predicted and actual visual consequences of the movement). One reason for this is that PEs tend to be associated with task errors, as well as changes in motor output and visual input, making them difficult to isolate. Here this issue is addressed using electroencephalography. A strategy (STR) condition, in which parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 107 publications
5
41
0
Order By: Relevance
“…As a matter of fact, the magnitude of postperturbation movement biases (Diedrichsen et al, 2005;Galea et al, 2015) is typically similar to the learning rate reported for implicit adaptation (Smith et al, 2006;McDougle et al, 2015). Interestingly, a recent electroencephalography (EEG) study has provided evidence that the parietal cortex may be involved in the directional reaching bias that emerges following single-trial exposure to a visuomotor rotation (Savoie et al, 2018). In that study, participants made reaching movements toward a visual target while being pseudorandomly exposed to a 45°visuomotor rotation (approximately every three trials).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…As a matter of fact, the magnitude of postperturbation movement biases (Diedrichsen et al, 2005;Galea et al, 2015) is typically similar to the learning rate reported for implicit adaptation (Smith et al, 2006;McDougle et al, 2015). Interestingly, a recent electroencephalography (EEG) study has provided evidence that the parietal cortex may be involved in the directional reaching bias that emerges following single-trial exposure to a visuomotor rotation (Savoie et al, 2018). In that study, participants made reaching movements toward a visual target while being pseudorandomly exposed to a 45°visuomotor rotation (approximately every three trials).…”
Section: Introductionmentioning
confidence: 59%
“…One way to probe for implicit adaptation is to expose individuals to an intermittent or randomly changing perturbation and to investigate the directional movement bias that occurs on the following trial (Diedrichsen et al, 2005;Galea et al, 2015;Torrecillos et al, 2015;Tan et al, 2016;Savoie et al, 2018). Indeed, this bias has been suggested to be automatic and nonstrategic (Donchin et al, 2003;Galea et al, 2015), which arguably make it a valid proxy for implicit adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a neurophysiological standpoint, the posterior parietal cortex (PPC) is often considered to be a key structure both for eye-hand coordination (Dean et al 2012;Hwang et al 2014;Van Donkelaar et al 2000) and for adaptation to visuomotor rotation (Haar et al 2015;Mutha et al 2011;Savoie et al 2018). Many neurons in PPC are influenced by both eye and hand actions (Carey 2000).…”
Section: Separate Contribution Of Eye Movements To Hand Tracking and mentioning
confidence: 99%
“…It has been proposed that the 75 P300 reflects the updating of a model of stimulus context (Donchin and Coles 1988). Both the FRN 76 and the P300 have been observed in response to errors in motor tasks (Krigolson et al 2008; Torrecil-77 los et al 2014;MacLean et al 2015;Reuter et al 2018;Savoie et al 2018) . In this paper we describe 78 experiments in which we isolated and compared EEG responses to both reward and sensory error 79 feedback using separate adaptation paradigms that produced comparable changes in behavior.…”
mentioning
confidence: 99%